2013
DOI: 10.2967/jnumed.112.118885
|View full text |Cite
|
Sign up to set email alerts
|

Influence of TSPO Genotype on 11C-PBR28 Standardized Uptake Values

Abstract: 11C-PBR28 binds to the high-affinity state of the translocator protein 18 kDa (TSPO). A single-nucleotide polymorphism (rs6971) within the human TSPO gene determines the affinity state of the TSPO. The rs6971 genotype determines whether individuals express the high-, low-, or mixed-affinity phenotype of TSPO. The rs6971 genotype corresponds to in vivo 11C-PBR28 binding, as measured quantitatively by total volume of distribution. However, it is not known whether standardized uptake value (SUV) can detect differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
52
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 18 publications
2
52
1
Order By: Relevance
“…This difference is larger than what was found in recent studies on Standardized Uptake Values (30 % difference, [29]) and V T (30-40 % difference [30,31], although the discrepancy was highly influenced by the outlier individual in the HAB group. Importantly, we could not show an effect of genotype on test-retest reproducibility, suggesting that genotype does not have to be controlled for in clinical studies with a within-subject experimental design.…”
Section: Discussioncontrasting
confidence: 71%
“…This difference is larger than what was found in recent studies on Standardized Uptake Values (30 % difference, [29]) and V T (30-40 % difference [30,31], although the discrepancy was highly influenced by the outlier individual in the HAB group. Importantly, we could not show an effect of genotype on test-retest reproducibility, suggesting that genotype does not have to be controlled for in clinical studies with a within-subject experimental design.…”
Section: Discussioncontrasting
confidence: 71%
“…and [(18)F]-FEPPA for imaging brain inflammation have been linked to this polymorphism (88,(93)(94)(95)(96). However, structural analyses have shown that A147T TSPO is able to retain the same structural profile as the wild-type protein, and binds the first generation TSPO ligand, PK 11195, with comparable affinity (97).…”
Section: Complications In the Application Of Certain Tspo Pet Ligandsmentioning
confidence: 99%
“…The Ala/Ala TSPO genotype (wild-type) results in high-affinity binding, whereas Ala/Thr results in mixed-affinity binding, and Thr/Thr results in low-affinity binding. MABs have 40%-50% lower binding potential for TSPO than do HABs (10)(11)(12). Because of the lack of binding in LABs, they are unsuitable for evaluation.…”
mentioning
confidence: 99%
“…However, their uptake is dependent on TSPO phenotype-high-affinity binders (HABs), low-affinity binders (LABs), and mixed-affinity binders (MABs) (10,11)-with a 40%-50% increase in binding potential for HABs compared with MABs, whereas LABs are unsuitable for evaluation. It is now clear that a nonsynonymous polymorphism of TSPO, coded by the rs6971 single-nucleotide polymorphism, affects the binding affinity of these tracers (10,11). This single-nucleotide polymorphism in exon 4 of the TSPO gene causes an alanine-tothreonine substitution in position 147.…”
mentioning
confidence: 99%